Sustained release of levofloxacin from thermosensitive chitosan‐based hydrogel for the treatment of postoperative endophthalmitis. Issue 1 (21st March 2019) - Cheng, Yung‐Hsin; Chang, Yu‐Fan; Ko, Yu‐Chieh; Liu, Catherine Jui‐ling
Abstract: In the field of ophthalmology, postoperative endophthalmitis (POE) is a serious surgical complication, which may lead to poor visual outcome even after the infection has been controlled. In the study, we develop a sustained drug releasing system loaded with levofloxacin which is expected to be effective against common pathogens responsible for POE for at least 7 days after single application at the end of surgery. The results of study showed that the sol–gel transition temperature of the levofloxacin‐loaded chitosan‐gelatin‐based solution was ~34°C. The gelation time of the developed formulation was ~81 s at 34°C. The results showed that the osmolality of developed hydrogel was 304 mOsm/L. The in vitro drug release studies revealed that levofloxacin release from the developed hydrogel displayed a sustained‐release profile. The long‐term antibacterial property of the developed hydrogel has been demonstrated. The biocompatibility of the developed hydrogel was evaluated in vitro . These results suggest that the levofloxacin‐containing hydrogel could be applied to ocular surface at the end of ophthalmic surgery, without the risks of intracameral injection of antibiotics. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 108B:8–13, 2020.